Vertical movements of Atlantic cod (Gadus morhua) in the Baltic and the North Sea ... - Neuenfeldt, Stefan; Payne, Mark; Righton, David; Der Kooij, Jeroen Vand (ASC 2009 - Theme session J, 2024)
No abstracts are to be cited without prior reference to the author.Vertical movements of Atlantic cod (Gadus morhua) in the Baltic and the North Sea. ...